2011
DOI: 10.1503/cmaj.100034
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival after cardiac or respiratory arrest in critical care units

Abstract: C ardiac arrest remains a major clinical and public health problem.1 Studies of cardiac arrest in volving patients admitted to non-critical care beds showed that survival has not improved despite 40 years of medical advances.2−4 Outside of critical care units, survival was substantially lower for nonwitnessed arrests than for witnessed arrests; for cardiac than for respiratory arrests; for arrests due to asystole or pulseless electrical activity than for those due to ventricular fibrillation or ventricular tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 42 publications
8
53
2
1
Order By: Relevance
“…For CPR in critical care units, a more recent study reports a 26.7% survival to discharge, with mortality increasing with duration of CPR and only one-third of patients surviving CPR which lasted more than 45 min. 8 Neither ACLS nor European Resuscitation Council (ERC) guidelines commit to a maximum duration of CPR before considering continued resuscitation futile, and both seem to conclude that rules for clinical decision-making cannot be recommended due to lack of prospective validation. 9,10 Other guidelines suggest that patient context, setting of cardiac arrest, and promptness and quality of resuscitation are the most important factors to consider.…”
Section: Discussionmentioning
confidence: 99%
“…For CPR in critical care units, a more recent study reports a 26.7% survival to discharge, with mortality increasing with duration of CPR and only one-third of patients surviving CPR which lasted more than 45 min. 8 Neither ACLS nor European Resuscitation Council (ERC) guidelines commit to a maximum duration of CPR before considering continued resuscitation futile, and both seem to conclude that rules for clinical decision-making cannot be recommended due to lack of prospective validation. 9,10 Other guidelines suggest that patient context, setting of cardiac arrest, and promptness and quality of resuscitation are the most important factors to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prior studies have suggested that survival after in-hospital CPR is higher when CPR is received in monitored settings [11][12][13][14]. Our findings of worse outcomes in monitored ventilated patients can be fully explained by the fact that these prior studies did not restrict their analyses to ventilated patients, who have a much higher severity of illness than non-ventilated patients.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, we cannot be certain that outcomes in Medicare beneficiaries have not also improved since 2005. Finally, we do not know the initial arrest rhythm, which is an important variable associated with survival [34], as survival rates are highest among patients with ventricular tachycardia or fibrillation [11][12][13]16,30,31,34,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of CPR, and initial cardiac activity did not significantly influence 30-day-mortality in our study, but earlier findings reported elevated mortality rate after nonshockable rhythms (20) and the duration of CPR as an independent predictor of mortality. (21,22) It is well known that the original ILCOR guideline recommended TH after ventricular fibrillation but for other rhythms the "may also be beneficial" statement was used. (6) In the present study, serum lactate levels in the TH group were significantly higher than in the NT group on ICU admission and in the 12 th and 36 th hours after ROSC.…”
Section: Protein S100b Levelsmentioning
confidence: 99%